Resilience of Philippine Folklore: An Enduring Heritage and Legacy for the 21st Century - Edgar R. Eslit (IJELR: International Journal of Education, Language, and Religion, 2023)
This qualitative study analyzed ten popular folklore in the Philippines to identify common themes and patterns related to Filipino values, beliefs, and traditions. The data was collected through a literature review, interviews with experts, and focus group discussions with select members of the community.  The use of modern technology was of the essence in the process. Journals, books, magazines, online sources, and calls were not spared. Thematic analysis was then used to identify key themes and patterns across the folklore gathered. The study found that folklore had significant cultural and historical significance and reflected the diversity of Philippine culture. The implications of the research for understanding the cultural heritage and identity of the Filipino people were discussed, as well as recommendations for promoting and preserving Philippine folklore in contemporary society. The limitations of the study were acknowledged, and directions for future research were suggested. Overall, the study highlights the importance of Philippine folklore as a means of understanding and preserving the country's cultural heritage.